2001
DOI: 10.1192/bjp.179.42.s4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of long-term antidepressant treatment

Abstract: BackgroundDepression, which only a few decades ago was considered to be a short-term illness requiring short-term treatment, is now recognised as a recurrent, sometimes chronic, long-term illness.AimsTo highlight the clinical importance of long-term antidepressant therapy in the treatment of depression.MethodThe current literature was reviewed to examine the relationship between duration of antidepressant therapy and efficacy.ResultsApproximately one-third to a half of patients successfully stabilised in acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 25 publications
1
38
0
5
Order By: Relevance
“…Long-term preventive maintenance of antidepressant treatment reduces the chance of recurrence by two-thirds (Geddes et al, 2003). Approximately 60% of such patients are at risk of experiencing a recurrent episode of depression within a year if left untreated, whereas those who continue antidepressant treatment have a recurrence rate of only 10-30% (see Hirschfeld, 2001). This beneficial treatment effect is similar across different classes of antidepressants, including SSRIs and selective NRIs.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term preventive maintenance of antidepressant treatment reduces the chance of recurrence by two-thirds (Geddes et al, 2003). Approximately 60% of such patients are at risk of experiencing a recurrent episode of depression within a year if left untreated, whereas those who continue antidepressant treatment have a recurrence rate of only 10-30% (see Hirschfeld, 2001). This beneficial treatment effect is similar across different classes of antidepressants, including SSRIs and selective NRIs.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with depression are treated in primary care, although often in a non-specific way (Kessler et al, 2003;Wilson et al, 2003). Adequate recognition and treatment can decrease the burden of disease (Claxton et al, 2000;Hirschfeld, 2001;Melfi et al, 1998). It is reported that general practitioners (GPs) recognize depression poorly, perhaps due to their more physical and demand-led orientation (Berardi et al, 2005;Simon and VonKorff, 1995;Wittchen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Continuation therapy for 16-20 weeks following remission is recommended for all patients with depression [American Psychiatric Association, 2000], and maintenance therapy should be considered for many patients. The risk of relapse and recurrence of depression can be significantly reduced if adequate continuation and maintenance therapy durations are achieved [Hirschfeld, 2001]. The safety and tolerability of duloxetine during long-term treatment (up to 52 weeks) have been investigated at doses of 80 and 120 mg/day [administered 40 mg twice daily and 60 mg twice daily, respectively; Raskin et al, 2003].…”
Section: Introductionmentioning
confidence: 99%